Unlocking sustainability: Exploring the benefits and challenges of implementing circular economy principles in the Maldives - Aminath Shaznie; Aishath Sinaau; Aishath Waheeda; Fathimath Muna; Wong Hoo (Heritage and Sustainable Development)
While circular economy offers a promising solution for issues in sustainability, this area remains unexplored in the context of Maldives. Hence, this paper explores the circular economy's complex environment, looking at its benefits, challenges, and implications for sustainable development. A concurrent mixed method design was used in the study, involving the simultaneous collection of quantitative and qualitative data, separate analysis, and integration during the interpretation phase. A total of 203 participants took part in the online survey and 17 participants took part in the interview. The quantitative data was analyzed by using descriptive statistical analysis and thematic analysis was used to analyze the qualitative data. As per the quantitative findings, the biggest challenges were identified as poor accountability of government organizations (3.97) and lack of infrastructure (3.97). Qualitative findings showed benefits such as reduced waste generation, enhanced resilience and sustainability, resource conservation, climate mitigation, and economic diversification. However, there are challenges to be overcome at both the micro and macroeconomic levels that were identified from this research. The findings of the research provide insight into circular economy benefits and challenges in Maldives, that could lead the government to draft effective policies and regulations. Moreover, the study’s findings contribute to the extant literature on the benefits and challenges of transitioning to a circular economy from a linear economy.